Kajian Model Empiris Minat Berwirausaha Siswa SMK di Kabupaten Garut - Rijal Assidiq Mulyana (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
The research was conducted to get the explanation and prove the influence of subjective norm, perceived behavioral control, and attitude toward theentreprenurial intention. the subject of research is the students of SMKN 12 Garut with the number of respondents 128 people, the analysis technique used is with the structural equations modelling. The results showed that subjective norms did not have a positive effect on perceived behavioral control, as well as on entrepreneurial attitudes. Meanwhile, subjective norm, perceived behavioral control, and entrepreneurial attitude simultaneously have no positive effect on entrepreneurial intention. but partially found a positive influence perceived behavioral control, and entrepreneurial attitudes towards entrepreneurial intention.